Coastal Clean-Up Campaign: A Community Response to Marine Litter in Pariaman City, Indonesia - Budi Riyanto; Arya Widiatmaja; Rosnani Rosnani; Syafni Yelvi Siska; Akbar Alim; Markus Asta Patma Nugraha; M. Fitriansyah Aldebaran; Muhammad Rizky Prima Sakti (Smart Society, 2026)
The coastal waste problem in Pariaman City, driven by rising plastic volumes, limited infrastructure, and disposal behaviors, threatens ecosystems and the tourism sector and requires coordinated intervention. This community service aims to implement an integrated cleanup with waste sorting and initial processing, while strengthening community capacity and environmental awareness. The “Coastal Clean-Up Campaign” applied a community-based participatory approach through coordinated clean-ups, source-level sorting, and initial composting. A total of 150 participants, including lecturers, students, village officials, and tourism stakeholders, were involved across 200-meter zones, supported by student-led scientific monitoring, before–after documentation, and the handover of bins and sorted waste to village authorities. The results indicate that the program was implemented effectively, with active stakeholder participation, visible environmental improvements, and the collection of 250 kg of sorted plastic and paper, some of which demonstrated economic value. This study presents a practical and replicable participatory model that integrates mass clean-up activities with source control, local governance support, and tourism stakeholder engagement. The findings highlight the importance of strengthening technical capacity, institutional support, periodic monitoring, and circular economy pathways to ensure sustainability. The program also increased environmental awareness and fostered local waste management groups, with outcomes that can support policy development and replication in other coastal tourism areas.